2020
DOI: 10.3917/th.831.0033
|View full text |Cite
|
Sign up to set email alerts
|

Supporting the design activity of farmers in transition to agroecology: Towards an understanding

Abstract: Pour faire face aux nombreux défis techniques, environnementaux et sociaux qui s’imposent à elle, l’agriculture doit changer. Parmi les voies possibles, l’agroécologie est une forme d’agriculture qui semble prometteuse. Elle repose sur l’idée de mobiliser les régulations biologiques et écologiques dans les champs pour développer des systèmes agro-alimentaires soutenables. Une telle forme d’agriculture nécessite une transformation du travail des agriculteurs, perçus non plus comme des utilisateurs de solutions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
0
8
0
1
Order By: Relevance
“…To highlight this, most of these authors proceed by a retrospective long-term analysis of the transition process (Lamine et al, 2009;Chantre et al, 2013;Coquil et al, 2017), based on farmers' narratives. Only a few undertake a longitudinal approach to transition in the making, as Chizallet et al (2020) have done.…”
Section: From An Analysis Of the Review To The Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…To highlight this, most of these authors proceed by a retrospective long-term analysis of the transition process (Lamine et al, 2009;Chantre et al, 2013;Coquil et al, 2017), based on farmers' narratives. Only a few undertake a longitudinal approach to transition in the making, as Chizallet et al (2020) have done.…”
Section: From An Analysis Of the Review To The Conceptual Frameworkmentioning
confidence: 99%
“…Our conceptual framework is a continuation of these approaches intended to show how learning and change can occur in the flow of a farmer's activities. As there is no unified definition of transition in the papers that we reviewed, We considered studies that consider sustainable transition as professional transformation (Chantre et al, 2015;Coquil et al, 2017;Chizallet et al, 2020). Following Masdonati and Zittoun (2012), we suggest that such transitions are characterized by three interdependent processes:…”
Section: Defining Professional Transitionmentioning
confidence: 99%
“…Inspiring examples, identified by tracking on-farm innovation or system experiments, can also support this exploration since they embody the systemic reasoning required to design scenarios of innovative agroecological systems (Goulet 2013;Salembier et al 2021). Exploration also helps farmers frame their issues and plans (Chizallet et al 2020). Several participatory design methods based on participants exchanging knowledge have been developed to organize this exploration, such as structured design spaces (e.g., KCP method, Berthet et al 2016), use of drawings or sketches (e.g., RIO method, Bos et al 2009;Elzen and Bos 2019) or simulation modeling (e.g., Rodriguez et al 2014).…”
Section: Innovative Research Pathsmentioning
confidence: 96%
“…Similarly, the "Chronicle of Change" method and its underlined tools (e.g. diagram tracing the design problem) have been developed "to keep track of past and ongoing design activity and to generate discussion around it" (Chizallet et al 2020). Moreover, researchers have shown that sharing examples from other domains and disciplines can be a useful source of inspiration (Bonnardel 2000).…”
Section: Developing Design-support Tools To Promote the Reuse Of Inno...mentioning
confidence: 99%